The Exogenous Application of Micro-Nutrient Elements and Amino Acids Improved the Yield, Nutritional Status and Quality of Mango in Arid Regions - Ahmed M. S. Kheir; Zheli Ding; Mohamed S. Gawish; Hanan M. Abou El Ghit; Taghred A. Hashim; Esmat F. Ali; Mamdouh A. Eissa; Zhaoxi Zhou; Mohammad S. Al-Harbi; Sherif Fathy El-Gioushy (Plants, 2021)
The mango is one of the most valuable and appealing tropical fruits due to its color, aroma, tasteful remarkable flavor, and nutritive value; however, improving the yield and quality of mango is an urgent goal in order to combat global population growth. The application of amino acids and a micronutrient mixture might improve the yield and quality features but further research is still required in arid regions. To study the combined effect of a micronutrient mixture (MM) and amino acids (AA) at different rates, twenty-seven Fagri Kalan mango trees (15 years old) were carefully selected. The foliar application effect of MM and AA on vegetative growth, total chlorophyll, leaf chemical constituents, productivity, and the fruit quality of mango trees (cv. Fagri Kalan) was investigated. The findings revealed that the investigated growth measurements and leaf chemical contents, as well as the fruiting aspects and the fruit quality improved significantly due to the application of MM and AA. A higher application rate of the micronutrient mixture (2 g L−1) in combination with the highest amino acid concentration (2 mg L−1) was the most effective combination that increased the yield, total soluble solids (TSS), total sugars (TS), and total carbohydrates by 28.0%, 3.0%, 5.8% and 15.0%, respectively, relative to untreated plants. The relationship between such characteristics revealed a strong positive correlation (0.80–0.95), confirming the importance of these materials in increasing the yield and quality of mangoes. Thus, using doses of MM and AA as a foliar spray four times during each growing season is recommended under similar environmental conditions and horticulture practices used in the current experiment.